A influência do tratamento periodontal no controle glicêmico em pacientes diabéticos tipo 2 não insulino-dependentes - Pereira, Dário da Rocha (2010)
Diabetes mellitus comprises a group of metabolic disorders that lead to hyperglycemia, and its main symptoms are polydipsia, polyuria, polyphagia and weight loss. In addition peripheral vascular disorders may impair wound healing and physiological changes that impair the immune response contribute to an increase risk of infections. Approximately 3-4% of patients undergoing dental treatment are diabetic, which is a risk factor for periodontal diseases. Some authors suggested that periodontal treatment in diabetic patients may contribute to the reduction of blood glucose levels. The aim of this study was to investigate the effects of periodontal treatment using "full mouth disinfection" without the use of antibiotics on glucose levels in type 2 diabetic non-insulin-dependent patients. A total of 15 individuals diagnosed with type 2 diabetes mellitus and periodontal disease were randomly divided into experimental and control groups. Glycemic levels of glycosylated hemoglobin and capillary and glucose rates were evaluated for a period of three months. Individuals in the test group received non-surgical periodontal treatment and were assessed on days 0, 30, 60 and 90. The control subjects were evaluated in the same period and received delayed periodontal treatment. Glycated hemoglobin levels decreased in both groups, but only in the test group, after 90 days, this reduction was statistically significant. The results of this study demonstrate that individuals with type 2 diabetes, insulin-dependent, which received non-surgical periodontal treatment, showed a significant reduction in levels of glycated hemoglobin after 3 months of therapy, while the control group did not show a statistically significant reduction. Within the limitations of this study, the data suggest a possible effect of periodontal therapy assistant in glycemic control in diabetic patients.